2013
DOI: 10.1002/jsfa.5989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal and non‐thermal pasteurisation on the microbial inactivation and phenolic degradation in fruit juice: a mini‐review

Abstract: Fruit juice has been traditionally preserved by thermal pasteurisation. However, the applied heat can cause detrimental effects on health-promoting components such as phenolic compounds. Several non-thermal technologies such as membrane filtration, pulsed electric field (PEF) and ultraviolet (UV) exposure are promising methods developed for liquid food preservation. In particular, the combination of UV and PEF has proven to be more effective for microbial inactivation and maintaining nutritional quality of fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 44 publications
5
54
0
Order By: Relevance
“…By the end of storage time, procyanidin B 2 and (-)-epicatechin showed an increase of 250 and 18% respectively compared to levels at time zero. Chen et al( 2013) reported that thermal processing may cause complex physical and chemical reactions affecting the phenolic composition, including the release of phenolic compounds from their bonded forms, degradation of polyphenols and the breakdown and transformation of phenolic compounds. Evolution of procyanidin B 2 and (-)-epicatechin during processing and storage (temperature and time) has been previously attributed to several reactions including depolymerisation of procyanidin polymers to oligomers (monomers, dimers, trimers, and tetramers), polymerisation, hydroxylation, esterification, epimerisation, thermal degradation, enzymatic and non-enzymatic oxidation and microbial degradation (Aron and Kennedy, 2008;Kaur and Kapoor, 2001;Keenan et al, 2011;Li et al, 2015).…”
Section: (-)-mentioning
confidence: 99%
“…By the end of storage time, procyanidin B 2 and (-)-epicatechin showed an increase of 250 and 18% respectively compared to levels at time zero. Chen et al( 2013) reported that thermal processing may cause complex physical and chemical reactions affecting the phenolic composition, including the release of phenolic compounds from their bonded forms, degradation of polyphenols and the breakdown and transformation of phenolic compounds. Evolution of procyanidin B 2 and (-)-epicatechin during processing and storage (temperature and time) has been previously attributed to several reactions including depolymerisation of procyanidin polymers to oligomers (monomers, dimers, trimers, and tetramers), polymerisation, hydroxylation, esterification, epimerisation, thermal degradation, enzymatic and non-enzymatic oxidation and microbial degradation (Aron and Kennedy, 2008;Kaur and Kapoor, 2001;Keenan et al, 2011;Li et al, 2015).…”
Section: (-)-mentioning
confidence: 99%
“…A number of foodborne outbreaks have been associated with the consumption of nontreated fruit juices (Aneja, Dhiman, Aggarwal, & Aneja, ; Aneja, Dhiman, Aggarwal, Kumar, et al., ; Vojdani, Beuchat, & Tauxe, ), that is why fruit juices production process usually integrates a pasteurization step in order to ensure their microbial safety and stability. However, the intensity of the heat treatment generally applied deteriorates the nutritional quality of fruit juices and modify their physicochemical and sensorial properties (Aneja, Dhiman, Aggarwal, Kumar, et al., ; Chen, Yu, & Rupasinghe, ; Jiménez‐Sánchez, Lozano‐Sánchez, Segura‐Carretero, & Fernández‐Gutiérrez, ,). These limitations have stimulated the research and the development of treatments with a minimal effect on the above properties of fruit juices (Cortés, Esteve, & Frígola, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, consumer demand for high‐quality, minimally processed, and microbiologically safe foods is increasing. Several low‐temperature technologies have been proposed, including irradiation, high hydrostatic pressure, pulsed electric fields, and ultraviolet (Chen et al., ; Jiménez‐Sánchez et al., ,; Rupasinghe & Yu, ). Unfortunately, the high initial investment required to acquire the technical equipment has limited their widespread use (Espina, Somolinos, Pagán, & García‐Gonzalo, ).…”
Section: Introductionmentioning
confidence: 99%
“…As for the 'yellow' beverages, the apple-RCW showed a higher total phenolic content and higher antioxidant activity than the pear-RCW beverage, whereas the blueberry-RCW beverage had a higher TPC, MAP, and AntOx, and a lower percent of polymeric color than the strawberry-RCW one (Table 6). Many studies have shown that thermal pasteurization can cause phenolic compounds to degrade in most fruit juice [39]. Noci et al [40] observed greater phenolic degradation in apple juice pasteurized at 94 • C, compared to that pasteurized at 72 • C. Also, the pasteurization time was shown to be an important factor that influences phenolic degradation in fruit juice.…”
Section: Influence Of Fruit Juice Type On Total Phenolics Total Anthmentioning
confidence: 99%